ESTUDO QUÍMICO E BIOATIVIDADE DE Baccharis semiserrata DC. - Mendes, Sayonara (2007)
The secondary metabolites found in leaves, stem bark and log extracts of Baccharis semiserrata DC. (Asteraceae) obtained in a Soxhlet apparatus with the sequence of solvents chloroform, ethyl acetate and methanol, were investigated using TLC and UV techniques. The analyses indicated that the phenolic compounds present in the organic extracts are mainly arylpropenoic acids or derivatives, that concentrate on the leaves ethyl acetate extract. The essential oil from the leaves obtained by steam distillation was GC-MS analyzed, and has spathulenol 25.8%, cadinene 16.7%, valencene 14.9% and aromadendrene 13.8% as the main components. The essential oils obtained by hydrodistillation from leaves of the feminine (0.13%) and masculine (0.45%) specimens of Baccharis semiserrata, collected in the Paraná State - Brazil, were analyzed in detail by GC and GC-MS. Both samples have low monoterpene content and they present the sesquiterpene spathulenol as the main component, reaching 50.75% in the oil of the masculine specimen and 42.65% in the feminine one. The antimicrobial activities of the organic extracts were measured against strains of the bacteria Bacillus cereus, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus and Staphylococcus saprophyticus, and of the microfungus Candida albicans, using diffusion techniques in solid mean, that resulted in moderate activity. The stem bark extracts usually were more active, especially the methanol extract against S. aureus. The minimum inhibitory concentrations of the essential oil were determined using the technique of dilution in broth, against S. aureus, P. aeruginosa and C. albicans (50/mL). The aqueous extract from leaves of feminine B. semiserrata showed the presence of saponins and proteins (4.963 mg/mL). The biochemical analysis of the interaction of human erythrocytes ABO+ with 1110/mL of the aqueous extract demonstrated an effect lithic pattern of + 80%, while 550/mL generated varied degrees of hemolysis. For the Oblood type the break only reached 35% in presence of the largest tested concentration. Such results suggest strongly the involvement of the antigenic portions of the system ABO (monosaccharides) and of the Rhesus protein (Rh+ and Rh-) in the observed effects. The aqueous extract when tested in presence of H2O2 and the serotype A+, showed a small reducer effect upon the liberated hemoglobin; for O- none effect could be observed. However, the scavenging capacity of the the aqueous extracts against DPPH radicals at 100M was enough significant: 1.5 x 10-1 and 7.8 x 10-2/mL of the extract reduced 15% and 20% of the sample, respectively.